2005
DOI: 10.2116/analsci.21.583
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Light Emitting Diode-Induced Fluorescence and Contactless Conductivity Detection for Capillary Electrophoresis

Abstract: A combined detection system of simultaneous contactless conductometric and fluorescent detection for capillary electrophoresis (CE) has been designed and evaluated. The two processes share a common detection cell. A blue lightemitting diode (LED) was used as the excitation source and an optical fiber was used to collect the emitting fluorescence for fluorescent detection (FD). Inorganic ions, fluorescein isothiocyanate (FITC)-labeled amino acids and small molecule peptides were separated and detected by the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…Tan et al [36] reported on the simultaneous fluorescence and CC detection for determination of labeled amino acids and small proteins [36]. However, CC detectors are mostly hyphenated with UV detectors [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [36] reported on the simultaneous fluorescence and CC detection for determination of labeled amino acids and small proteins [36]. However, CC detectors are mostly hyphenated with UV detectors [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, offline FITC-labeled AAs were separated and detected by the combined detector, the LODs were in the submicromolar level [14].…”
Section: Ce/fluorescencementioning
confidence: 96%
“…Tan et al [36] reported a combined detection system using contactless conductometric detection and fluorescent detection for CE in a common cell. A blue LED was used for the excitation source, and an optical fiber was used to collect the fluorescence.…”
Section: Jong and Lucymentioning
confidence: 99%